FREQUENCY OF HIGH DEGREE AV BLOCKS IN ACUTE INFERIOR MYOCARDIAL INFARCTION AND THEIR IMPACT ON CLINICAL OUTCOMES: High Degree AV Blocks in Acute Inferior MI - Mehreen, Sobia; Ahmed, Adeel; Tahir, Muhammad (Pakistan Armed Forces Medical Journal, 2016)
Objective: To evaluate the frequency of high degree AV block in acute inferior wall myocardial infarction and to compare in hospital clinical outcomes in patients with inferior wall MI with and without AV Block.Study Design: Cross sectional descriptive study.Place and Duration of Study: Study was carried out at Armed Forces Institute of Cardiology, National Institute of Heart Diseases (AFIC-NIHD) Rawalpindi from Nov 2011 to June 2012, on patients admitted with acute inferior MI.Patients and Methods: Standard 12 lead ECG was recorded immediately after admission. Diagnosis of acute inferior wall MI was made in the presence of ST elevation >0.1 mv (1mm) in two or more of leads II, III and aVF. Continuous bed side cardiac monitoring was carried out. Two groups were made out of 193 patients. GROUPA (AVB+)=Patients having acute inferior wall infarction with AV block, GROUPB (AVB-)Patients having acute inferior wall infarction without AV block. Each group was compared for different variables. Data analysis was done by SPSS 17 statistical software.Results: AVB was found in 54 of 193 patients with inferior wall MI (28%). Five patients (9.25%) of group A and 2 patients (1.43%) of group B died during hospital stay showing significantly higher mortality in patients with AVB (p=0.009).Conclusion: Heart blocks are frequent among patients with inferior wall MI and are accompanied with a variety of in hospital complications. These complications can be minimized by early recognition and timely management including interventions like temporary cardiac pacing.